Pengaruh Vanity Seeking, Purchase Experience, Dan Celebrity Endorser, Pada Minat Beli Ulang Dengan Sikap Terhadap Laneige Sebagai Variabel Mediasi - Herry Maridjo; Povy Amelia (JEMAP, 2020)
This research aims to determine: 1) the influence of vanity seeking on repurchase intention with attitude toward laneige as a mediating variable, 2) the influence of purchasing experience on repurchase intention with attitude towards laneige as a mediating variable, 3) the influence of celebrity endorser on repurchase intention with attitude toward laneige as a mediating variable. The population in this research is Laneige consumers who have already bought Laneige with a total sample of 96 respondents. The sampling technique used is convenience sampling. The sampling technique used is convenience sampling. The validity test uses the construct validity test of convergent and discriminant constructs, and reliability test uses the formula of composite reliability and Cronchbach’s alpha. The data analysis technique used in this research is SEM using Partial Least Squares (SEM-PLS). The results showed that: 1) Vanity seeking did not have a positive influence on repurchase intention with attitudes toward Laneige as a mediating variable, 2) Purchase experience had a positive influence on repurchase intention with partial mediation by attitudes towards Laneige, 3) Celebrity endorser had positive influence on repurchase intention with full mediation by the attitude towards Laneige.